ANALISIS MODERASI BERAGAMA DALAM MENGEMBANGKAN KARAKTER INKLUSIF PESERTA DIDIK SMAN 15 BANDAR LAMPUNG - Kurnia Saputra, Adi; Mona Adha, Muhammad; Halim, Abdul; Nurmalisa, Yunisca; Permata Sari, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on the forms of religious moderation practices, the supporting and inhibiting factors, as well as their contribution to shaping inclusive character as reflected through students’ attitudes of tolerance, empathy, and inclusive communication. The research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving students, teachers, and school authorities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity ensured through triangulation. The results show that religious moderation practices are manifested through the implementation of worship activities for three religions and the fair attitude of teachers in the classroom, such as equitable group division without distinguishing students’ religious backgrounds. Religious moderation plays a role in forming students’ tolerance, which is reflected in mutual respect when other religious groups are performing worship by not causing disturbances. In addition, religious moderation fosters empathy and social concern through activities such as reminding one another about worship, providing social assistance during floods, visiting orphanages, and supporting peers who experience difficulties in social interaction. Religious moderation also builds inclusive communication, where teachers’ fair responses to differences encourage students to express opinions and participate in discussions without fear of being blamed or discriminated against, resulting in open and respectful communication. Supporting factors of religious moderation include a school culture that upholds tolerance, opportunities for worship for all religions, and students’ awareness and positive attitudes toward diversity. Meanwhile, inhibiting factors include differences in students’ individual social characteristics and the potential for joking remarks that may lead to ridicule.